Radiocarbon Dating of the Nyixoi Chongco Rock Avalanche, Southern Tibet: Search for Signals of Seismic Shaking and Hydroclimatic Events - Ha, Guanghao; Liu, Feng; Cai, Maotang; Pei, Junling; Yao, Xin; Li, Lingjing (Frontiers in Earth Science, 2022)
Landslides are recognized as being important agents of surface processes in the growth of mountainous topography. Dating prehistorical landslide is an important prerequisite for establishing relationships between prehistoric slope instability and past climatic regimes or paleo-seismic records. The Nyixoi Chongco rock avalanche (NCRA) located in the Angang graben within the N–S trending rift zone in southern Tibet, is a giant prehistorical mass wasting event that is characterized by exceptional mobility and large volume. However, the exact emplacement time and origin of the NCRA are still controversial. Here, we present our study involving 14C dating of peat layers and snail shells to constrain the emplacement age of the NCRA. The 14C age of the organic material and plant remnants from the basal peat layer are 1272-1389 and 1299-1404 cal AD, respectively. The 14C ages dated from aquatic snail shells and bog overlying the rock avalanche are 425-565 and 1022-1159 cal AD, respectively. These results reflect that there were at least two separate and distinct events which occurred in the NCRA, instead of a single event suggested by previous studies. With field investigation and temporal correlation, we believe that there are no paleo-seismic records in the Angang graben that would corroborate a co-seismic trigger of the NCRA. Therefore, we suggest that 14C ages from sediments below or above the landslide rocks should be interpreted carefully. It is not enough to infer the true trigger of the NCRA event at present based on 14C ages alone.